Successful Treatment of Sinusitis by Acanthamoeba in a Pediatric Patient After Allogeneic Stem Cell Transplantation. Issue 12 (December 2016) - Juan, Antonio; Alonso, Laura; Olivé, Teresa; Navarro, Alexandra; Sulleiro, Elena; Sánchez de Toledo, José; Díaz de Heredia, Cristina
Abstract : Acanthamoeba infections are rare and mostly occur in immunocompromised patients. Most of the reported cases after stem cell transplantation have been diagnosed postmortem. We present the case of a 3-year-old boy with chronic graft versus host disease post hematopoietic transplantation, who was successfully treated for Acanthamoeba.